Motivational Aspect of Organizational Culture in the Quality Management System at the Enterprise - Maksymenko, І.О.; Uzun, M.V. (Економічний вісник Донбасу, 2014)
The article is devoted to the analysis of the range of issues associated with the review of the impact of organizational culture on the effectiveness of motivational mechanism of strategic management. Describes the features of the close link in the chain of organizational culture-motivation-efficiency of the company. It is established that a high level of organizational culture is a key factor in the long-term success of the enterprise, due to the influence on motivation of labor activity of the personnel. It’s determined a dependence of the willingness of companies to implement large-scale transformations of the implementation of strategies to improve product quality from their organizational goals and values employees. It’s grounded the necessity of creation of effective, adaptive to new requirements, the mechanism of motivation of the personnel, as an important condition of effective activity of the company. The study revealed the influence of employee motivation on product quality. It is established that organizational culture unites staff motivation and strategy of the company. Authors propose a complex of directions for the formation of an effective organizational culture as a factor of motivation of the personnel in the quality management system at the enterprise. Стаття присвячена аналізу кола питань, пов’язаних із розглядом впливу організаційної культури на ефективність мотиваційного механізму в процесі стратегічного управління підприємством. Розглянуто особливості тісного взаємозв’язку в ланцюгу організаційна культура-мотивація-ефективність діяльності компанії. Встановлено, що високий рівень організаційної культури виступає ключовим фактором довгострокового успіху підп- риємства, за рахунок впливу на мотивацію трудової діяльності персоналу. Визначена залежність готовності компаній здійснювати масштабні перетворення з впровадження стратегій підвищення якості продукції від їх цілей та організаційних цінностей працівників. Обґрунтовано необхідність створення дієвого, адаптивного до нових вимог, механізму мотивації праці персоналу як важливої умови ефективної діяльності компанії. В ході дослідження виявлено вплив мотивації працівників на якість продукції. Встановлено, що організаційна культура поєднує мотивацію персоналу і стратегію підприємства. Запропоновано комплекс напрямків щодо формування ефективної організаційної культури як чинника мотивації персоналу в системі управління якістю на підприємстві. Статья посвящена анализу круга вопросов, связанных с рассмотрением влияния организационной культуры на эффективность мотивационного механизма в процессе стратегического управления предприятием. Рассмотрены особенности тесной взаимосвязи в цепи организационная культура-мотивация-эффективность деятельности компании. Установлено, что высокий уровень организационной культуры выступает ключевым фактором долгосрочного успеха предприятия, за счет влияния на мотивацию трудовой деятельности персонала. Определена зависимость готовности компаний осуществлять масштабные преобразования внедрения стратегий повышения качества продукции от их целей и организационных ценностейработников. Обоснована необходимость создания действенного, адаптивного к новым требованиям, механизма мотивации труда персонала как важного условия эффективной деятельности компании. В ходе исследования выявлено влияние мотивации работников на качество продукции. Установлено, что организационная культура объединяет мотивацию персонала и стратегию предприятия. Предложен комплекс направлений по формированию эффективной организационной культуры как фактора мотивации персонала в системе управления качеством на предприятии.